STYLE IN YORUBA CRIME-FICTION (1993)
Crime, the bane of contemporary society has attracted the attention of many scholars in the Social Sciences. Literary writers have also made crime a subject-matter in their works. In their own case, Yoruba prose-fiction writers present various facets of crime and crime-detection in their works. Using the content of the modern Yoruba novels, Ogunsina (1976) and lsola (1978) have identified crime-fiction as a major class of Yoruba prose-fiction. Critical works such as Ogunsina (1976, 1987) and Olufajo (1988) on this class of Yoruba prose-fiction are mainly historical and sociological. While Ogunsina (1976:202-205) explains that language use in the modern Yoruba novel is in conformity with modern usage, Isola (1978: 190-260) classifies the use of language in the modern Yoruba novel into three: casual, mixed styles and elegant. Hitherto, critical works on Yoruba prose-fiction have only limited their activities to the use of subjective evaluative terms like good or bad and casual or polished to describe a novelist's style. The focus of this thesis therefore, is to identify and analyse the style of Yoruba crime fiction writers in order to arrive at a more acceptable stylistic description of this class of Yoruba prose-fiction. The work is in two parts. The first part which consists of two chapters forms the background study. Here, attempt is made to situate the problem of crime within the sociological background with the aim of placing Yoruba crime-fiction in proper perspective. The issue of style is also examined in this part. In the second part which comprises four chapters, an indepth analysis of the works of two prominent Yoruba crime-fiction writers: Okediji and Akinlade is attempted. The writers' narrative presentationa, styles, characterizational style and their use of language are discussed in this section. We conclude that, despite the differences in the writers' works, Okediji's and Akinlade's language serve ultimately the same purpose: to impose order upon chaos, to give structure and• meaning to the secret travail which ordinary life conceals.